Analysis of Airway and Midface in Crouzon Syndromes. Issue 6 (June 2019) - Forte, Antonio J.; Lu, Xiaona; Hashim, Peter W.; Steinbacher, Derek M.; Alperovich, Michael; Persing, John A.; Alonso, Nivaldo
Abstract : Background: Crouzon syndrome is associated with severe respiratory impairment of the upper airway due in part to midfacial dysmorphology. We calculated the distinctive nasal diameter and pharyngeal airway volume in patients with Crouzon syndrome and compared them with age-matched control subjects. Methods: Children with computed tomography scans in the absence of surgical intervention were included. Computed tomography scans were digitized and manipulated using Surgicase CMF (Materialise). Craniometric data relating to the midface and airway were collected. For all linear measurements, mean percent increases or decreases were calculated relative to the size of control subjects, and volumetric assessment of the airway was tabulated. Statistical analysis was performed using t test. Results: Twenty-six computed tomography scans were included (control n = 17, Crouzon n = 9). All children were in early mixed dentition. Pharyngeal airway volume was decreased in patients with Crouzon syndrome relative to control subjects by 46% ( P = 0.003). The distance from the posterior tongue to the posterior pharyngeal wall decreased 31% when comparing the Crouzon group versus the control ( P = 0.04). Conclusions: Three-dimensional analysis revealed notably decreased pharyngeal and nasal airway volumes in patients with Crouzon syndrome, but nasal bone tissue and soft tissue measurements showed very little change between patients and control subjects.